Impact of Perceptual Dimensions and Behavioral dimension on brand equity in Pakistan - Shabbir, Javeria (Information Management and Business Review, 2013)
The purpose of this study is to investigate the effects of consumer-based brand equity dimensions on Pakistani mobile branded market. To do this, data were collected through convenient sampling from 250 consumers of mobile users from Universities and shopping malls. Islamabad and Rawalpindi were selected for data collection. Through self-administered questionnaire based surveys in order to investigate the mobile’s brand as product. The analysis involved Regression and Mean values that, all alternative hypotheses have been accepted. The regression analysis results show all dimensions positively and significantly, influences brand equity. This research study is important in identifying the sources of brand equity in Pakistan’s mobile industry. This is the first study investigating the perceptual and behavioral dimension of consumer-based brand equity of mobile brand in Pakistan. Hence, it makes a contribution for both marketer and practitioners for devising strategies.